Application of LabVIEW to Communicating between PC and Training Model of Electronic Fuel Injected Engine - Đỗ, Văn Dũng; Huỳnh , Quốc Việt; Nguyễn , Văn Long Giang; Trần , Thế Liên (Journal of Technical Education Science, 2010)
This paper presents the application of LabVIEW to communicating between PC (Personal Computers) and training model of electronic fuel injected engine. The new engine training models have the program to use LabVIEW to perform experiments to build performance characteristics of the engine for researching and learning purposes. On the other hand, the program interface allows users to change main parameters in various operating conditions of the engine such as fuel injection duration, coolant temperature, intake of air temperature, airflow... The program interface also allows students to study troubleshooting on the engine model.